2021
DOI: 10.1021/acsinfecdis.1c00087
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Antimicrobial and Antibiofilm Activity of Human Milk Lactoferrin Compared to Bovine Lactoferrin against Multidrug Resistant and Susceptible Acinetobacter baumannii Clinical Isolates

Abstract: Acinetobacter baumannii is an opportunistic bacterial pathogen that causes severe infections in immunocompromised patients. The emergence of multi- and pan-drug resistant strains of A. baumannii from clinical sources has confounded treatment and enhanced morbidity and mortality associated with these infections. One way that A. baumannii circumnavigates environmental and antimicrobial challenge is by forming tertiary architectural structures of cells known as biofilms. Biofilm-inhibiting molecules could be depl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…Lactoferrin's binding affinity for iron is 300 times higher than that of transferrin. These observations provide evidence that indicates the complex interplay between this pathogen's and both human and bovine isoforms of host products [42]. Together, these observations demonstrate how human proteins can have an important and significant impact on biofilm formation.…”
Section: Hsa and Hs Negatively Affects Biofilm Formationmentioning
confidence: 58%
See 1 more Smart Citation
“…Lactoferrin's binding affinity for iron is 300 times higher than that of transferrin. These observations provide evidence that indicates the complex interplay between this pathogen's and both human and bovine isoforms of host products [42]. Together, these observations demonstrate how human proteins can have an important and significant impact on biofilm formation.…”
Section: Hsa and Hs Negatively Affects Biofilm Formationmentioning
confidence: 58%
“…Another human molecule that also exhibited biofilm formation inhibition in A. baumannii strains was L-Adrenaline [41]. In addition, a recent study reported that lactoferrin has antimicrobial and antibiofilm activities against A. baumannii clinical strains that were isolated from wounds, blood, urine, and sputum/bronchial wash [42]. Lactoferrin is an innate immune glycoprotein produced in high concentrations in both human and bovine milk, and is considered one of the most effective iron chelators.…”
Section: Quorum Network Is Altered By Hsa and Hsmentioning
confidence: 99%
“…The utility of human milk as a prebiotic that can protect against a variety of infections has been well demonstrated in the literature. ,, Infants whose primary source of nutrition, which is derived from human breast milk, have enhanced protection against diarrhea, respiratory infection, urinary tract infection, ear infection, necrotizing enterocolitis (NEC), and specifically, infection with Escherichia coli , Clostridioides difficile , and Campylobacter jejuni . Human milk harbors a variety of antimicrobial molecules that can inhibit the growth and viability of a variety of pathogenic microbes as well as immune-modulating molecules that influence inflammation responses to invading pathogens . Our recent work and the work of others has demonstrated that the human milk glycoprotein lactoferrin has antimicrobial and antibiofilm activities against A. baumannii and other bacteria, including S. agalactiae , S. aureus , and Pseudomonas aeruginosa . In addition to the proteinaceous components of milk, the human milk glycome is also of particular interest, as components within this population of molecules have been associated with strong protection against infection by enteric pathogens …”
Section: Discussionmentioning
confidence: 99%
“…Human AMP LL37 is one such AMP that inhibits A. baumannii biofilm ( 291 ). Human milk lactoferrin which is an iron-chelating AMP also showed slightly more potent antibacterial activity than bovine milk lactoferrin against A. baumannii biofilm ( 292 ). Derivative (D-RR4) of a small synthetic peptide, RR (12 amino acids) exhibited potent antibacterial and anti-biofilm activity against P. aeruginosa and A. baumannii in macrophage cells as well as in a Caenorhabditis elegans model ( 293 ).…”
Section: Strategies Of Preventing a Baumannii Biof...mentioning
confidence: 99%